2017
DOI: 10.1155/2017/5291486
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofStreptococcus sanguinisBacteriocin on Deformation, Adhesion Ability, and Young’s Modulus ofCandida albicans

Abstract: In order to study the thallus changes on microscopic morphology and mechanical properties of Candida albicans antagonized by Streptococcus sanguinis bacteriocin, the adhesion ability and Young's modulus of thalli and hypha of Candida albicans were measured by the relative measurement method using atomic force microscope's (AFM) tapping model. The results showed that the average adhesion ability and Young's modulus of thalli were 7.35 ± 0.77 nN and 7.33 ± 1.29 Mpa, respectively; the average adhesion ability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Despite the sizeable number of prior AFM studies that use C. albicans cells, there are only a few studies that specifically focus on hyphal cells (25,28,(37)(38)(39)(40)(41)(42). In these studies, hyphae were grown from a culture for several hours and then immobilized on a substrate using either chemical fixation or hydrophobic coatings, and measurements were performed at room temperature either in buffered medium or under dry conditions.…”
mentioning
confidence: 99%
“…Despite the sizeable number of prior AFM studies that use C. albicans cells, there are only a few studies that specifically focus on hyphal cells (25,28,(37)(38)(39)(40)(41)(42). In these studies, hyphae were grown from a culture for several hours and then immobilized on a substrate using either chemical fixation or hydrophobic coatings, and measurements were performed at room temperature either in buffered medium or under dry conditions.…”
mentioning
confidence: 99%
“…Yeast cell rigidity is strongly associated with yeast cellular structure [ 47 ], which can be modified in response to external stress [ 48 , 49 , 50 , 51 , 52 ]. C. albicans cells have been reported to increase their cell rigidity in response to various factors, such as the alteration of the nutrient medium [ 53 , 54 ], exposure to ethanol [ 48 ], a compromised or removed mannan layer in the cell wall [ 47 ], or the echinocandins-induced inhibition of β-1,3-glucan synthase, an enzyme involved in cell wall synthesis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the authors detected that bacteria-induced nanoscale changes in the roughness of the fungal LG-8 surface played a role in assisting the adhesion process [ 114 ]. Another study was carried out by Ma et al and showed the effects of bacteriocins released by Streptococcus sanguinis on the mechanical properties of C. albicans [ 115 ]. S. sanguinis is a well-known dominant bacteria in healthy human oral cavity, reported to help to exert an antagonistic effect on C. albicans, thus protecting the oral cavity against fungal-induced disbalance of microbiota.…”
Section: Afm-based Investigation As a Novel Approach To Fight Withmentioning
confidence: 99%
“…Analogical observation was noted for adhesion ability, which deceased after treatment with bacteriocins. All of the measurements were performed with tapping mode [ 115 ].…”
Section: Afm-based Investigation As a Novel Approach To Fight Withmentioning
confidence: 99%